PENGUKURAN TINGKAT KEBUGARAN SISWA SEKOLAH DASAR DI WLAYAH KERJA PUSKESMAS KASSI-KASSI KOTA MAKASSAR - Liza Fauzia; Eva Arna Abrar; Fitri A. Sabil; Nurul Rezki Anisa; Anwar Ganing (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Physical fitness is a crucial aspect in supporting students' health and academic performance. This activity aims to determine the cardiorespiratory fitness levels of junior high school students using the Rockport Walk Test method. This method was chosen for its safety, practicality, and effectiveness in estimating VO?max through a 1.0 km walking activity. The subjects were 75 elementary school students who completed the test, with data collected on walking time, heart rate, age, gender, and body weight. The results showed that the majority of students were in the very poor (82,2%) to moderate category (8.9%), with an average VO?max of 30.1 ml/kg/min. The result indicated a need for more regular physical activity. This activity concludes that the Rockport method is effective for monitoring student fitness and can serve as a basis for designing physical education programs in schools.